2019
DOI: 10.2106/jbjs.18.01256
|View full text |Cite
|
Sign up to set email alerts
|

Not All Garden-I and II Femoral Neck Fractures in the Elderly Should Be Fixed

Abstract: Background: Internal fixation is currently the standard of care for Garden-I and II femoral neck fractures in elderly patients. However, there may be a degree of posterior tilt (measured on preoperative lateral radiograph) above which failure is likely, and primary arthroplasty would be preferred. The purpose of this analysis was to determine the association between posterior tilt and the risk of subsequent arthroplasty following internal fixation of Garden-I and II femoral neck fractures in elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 19 publications
3
64
0
Order By: Relevance
“…The total reoperation rate in our study population was 25%, and 16% of the patients underwent conversion to arthroplasty. These findings are similar to those of previous studies, which have reported reoperation rates between 16% and 33% (Palm et al 2009, Lapidus et al 2013, Bartels et al 2018, Nyholm et al 2018, Okike et al 2019, Stockton et al 2019. Reoperation rates have been found to vary in the literature depending on which operations were defined as J o u r n a l P r e -p r o o f relevant reoperations (Nyholm et al 2018, Stockton et al 2019).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The total reoperation rate in our study population was 25%, and 16% of the patients underwent conversion to arthroplasty. These findings are similar to those of previous studies, which have reported reoperation rates between 16% and 33% (Palm et al 2009, Lapidus et al 2013, Bartels et al 2018, Nyholm et al 2018, Okike et al 2019, Stockton et al 2019. Reoperation rates have been found to vary in the literature depending on which operations were defined as J o u r n a l P r e -p r o o f relevant reoperations (Nyholm et al 2018, Stockton et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Further, there was no difference in risk of conversion to arthroplasty between patients with non-displaced FNF with a <0° or ≥20° posterior tilt and patients with displaced FNF, suggesting that the effect of posterior tilt on later failure of internal fixation is as important as displacement on the AP radiograph. Comparably to our results, Okike et al reported an increased risk of later conversion to arthroplasty in patients with a posterior tilt of ≥20° (Okike et al 2019). Stockton et al reported a conversion-to-arthroplasty rate of 14% in patients aged 18-50 years (Stockton et al 2019).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Osteonecrosis of femoral head and nonunion were the primary causes for reoperation after internal fixation. Furthermore, high preoperative anterior tilt or posterior tilt, low bone mineral density, patient age, gender, and higher body mass could increase the risk of reoperation in Garden I and II femoral neck fractures treated with cannulated screws 21–25 . Screw fixation could not provide a satisfactory long‐term reoperation rate in elderly patients with undisplaced femoral neck fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In internal xation of femoral neck fractures, xation failure is not uncommon, and no consensus has been reached regarding the optimal xation construct. Preoperative posterior tilt (or retroversion) of the femoral head has been recognized as an important risk factor for xation failure of femoral neck fractures [3][4][5]. Since retroversion of the femoral head would largely cause damage of the posterior cortex and/or weaken the osseous mechanical transduction, the fracture would still present with posterior instability even after anatomic reduction.…”
Section: Introductionmentioning
confidence: 99%